(-9)^20 ori (-1/27)^30 ori (-1/3)^49
Răspunsuri la întrebare
Răspuns de
1
=[(-3)²]²°x[(-1/3)³]³°x(-1/3)⁴⁹=
=(-3)⁴°x(-1/3)⁹⁰x(-1/3)⁴⁹=
=(-3)⁴⁰x(-1/3)⁹⁰⁺⁴⁹=
=(-3)⁴⁰x(-3)⁻¹³⁹=
=(-3)⁴°⁻¹³⁹=(-3)⁻⁹⁹=(-1/3)⁹⁹
=(-3)⁴°x(-1/3)⁹⁰x(-1/3)⁴⁹=
=(-3)⁴⁰x(-1/3)⁹⁰⁺⁴⁹=
=(-3)⁴⁰x(-3)⁻¹³⁹=
=(-3)⁴°⁻¹³⁹=(-3)⁻⁹⁹=(-1/3)⁹⁹
Mirela27:
Ms din sufleet\
Alte întrebări interesante
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Fizică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă